1991
DOI: 10.1111/j.1365-2958.1991.tb02123.x
|View full text |Cite
|
Sign up to set email alerts
|

P.70 pertactin, an outer‐membrane protein from Bordetella parapertussis: cloning, nucleotide sequence and surface expression in Escherichia coli

Abstract: The gene prn encoding the outer-membrane protein P.70 (pertactin) from Bordetella parapertussis has been cloned in Escherichia coli and its DNA sequence determined. Analysis of the DNA sequence reveals that the gene has an open reading frame comprising 922 amino acids capable of encoding a protein with a molecular weight of 95,177 (P.95). In vivo processing of this precursor yields a protein with an estimated Mr of 70 kDa (P.70) which is located on the surface of B. parapertussis. Homology between the prn gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 46 publications
1
44
1
Order By: Relevance
“…An additional human isolate, 97-219, was reported, paradoxically, as having both the 1-4a1/2-6a1 and the 1-3a/2-6a1 alleles (Diavatopoulos et al, 2005). The region 1 variant 1-4a1 has additionally been reported for 12 human isolates of Bordetella parapertussis, but accompanied only by region 2 sequences comprising eight to ten PQP repeats (Li et al, 1991;Mäkinen et al, 2003;Diavatopoulos et al, 2005;Bouchez et al, 2011). In B. bronchiseptica, 1-4a1 has been found in association with only the six-repeat region 2 variant 2-6a1 Isolate 22/M63/4/09, the sole seal isolate in our study with a genotype found in other hosts (RT1/ST14), was cultured from the intestine of a dead seal recovered on the Atlantic coast of south-west England.…”
Section: Discussionmentioning
confidence: 99%
“…An additional human isolate, 97-219, was reported, paradoxically, as having both the 1-4a1/2-6a1 and the 1-3a/2-6a1 alleles (Diavatopoulos et al, 2005). The region 1 variant 1-4a1 has additionally been reported for 12 human isolates of Bordetella parapertussis, but accompanied only by region 2 sequences comprising eight to ten PQP repeats (Li et al, 1991;Mäkinen et al, 2003;Diavatopoulos et al, 2005;Bouchez et al, 2011). In B. bronchiseptica, 1-4a1 has been found in association with only the six-repeat region 2 variant 2-6a1 Isolate 22/M63/4/09, the sole seal isolate in our study with a genotype found in other hosts (RT1/ST14), was cultured from the intestine of a dead seal recovered on the Atlantic coast of south-west England.…”
Section: Discussionmentioning
confidence: 99%
“…The pertactin genes of isolates used in this study were sequenced previously or in this study (Mooi et al, 1998Mastrantonio et al, 1999 ;Li et al, 1991) (Table 1). Except for the clinical isolates, the prn genes were sequenced completely on both strands.…”
Section: Methodsmentioning
confidence: 99%
“…Most likely, the major antigenic domains take place in the C-terminal region containing proline-rich repeat units, known to be highly immunoreactive and involved in the binding of surface-exposed adhesive molecules to host cells. 1,7,13,18 Further investigation is needed to determine the immunodominant fragments of the M. gallisepticum PvpA cytadhesin and to evaluate their adhesive functionality.…”
Section: In Comparison Withmentioning
confidence: 99%